2008
DOI: 10.1177/0142723708092413
|View full text |Cite
|
Sign up to set email alerts
|

Young children's yes bias: How does it relate to verbal ability, inhibitory control, and theory of mind?

Abstract: The aim of the present study was to investigate how young children reduce a yes bias, the tendency to answer 'yes' to yes-no questions. Specifically, we examined three possible factors: verbal ability, inhibitory control and theory of mind. Results revealed that verbal ability and inhibitory control were strongly associated with a yes bias even after controlling for age. Regression analyses revealed that these two factors significantly predicted a yes bias. Theory of mind was not significantly correlated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
42
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 30 publications
(38 reference statements)
1
42
0
Order By: Relevance
“…Crain and Thornton (2000) claim that young children have a yes-bias, but other works present a more complicated picture (cf. Fritzley andLee 2003, Moriguchi, Okanda, andItakura 2008, a.o.-thanks to a reviewer for drawing our attention to these works). conclusion).…”
Section: 'Preference For Truth'mentioning
confidence: 98%
“…Crain and Thornton (2000) claim that young children have a yes-bias, but other works present a more complicated picture (cf. Fritzley andLee 2003, Moriguchi, Okanda, andItakura 2008, a.o.-thanks to a reviewer for drawing our attention to these works). conclusion).…”
Section: 'Preference For Truth'mentioning
confidence: 98%
“…Okanda and Itakura (2010b) proposed that younger and older preschoolers might exhibit response biases due to different mechanisms. They noted that cognitive abilities such as inhibitory control abilities and language skills could contribute to younger preschoolers' tendencies to exhibit a yes bias (see also Moriguchi, Okanda, & Itakura, 2008;Okanda & Itakura, 2007): young preschoolers might exhibit a yes bias automatically because they cannot inhibit a ''yes'' response or because they do not understand the context of the questions. For older preschoolers, Okanda and Itakura (2010b) suggested that there are more social reasons for choosing ''yes'' or ''no'' responses. In this study, we examined children's response latency to yes-no questions to provide support for the idea that younger and older preschoolers exhibit a yes bias due to different mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Prior research has found that children’s lies are related to executive functioning (Talwar & Lee, 2008). Because we controlled for yes-bias (which is related to inhibitory skills; Moriguchi, Okanda, & Itakura, 2008), we believe that young children’s ability to make false statements reflects something more specific than simply impulsive responding. Nevertheless, inhibitory abilities probably play some role in facilitating false statements because children’s repeated experience with labeling objects leads true statements to function as prepotent responses.…”
Section: Discussionmentioning
confidence: 99%